Relationship between refractive error, axial length and macula thickness in Malay subjects / Noor Hidayah Mohamad … [et al.] - Mohamad, Noor Hidayah; Vasudevan, Sushil Kumar; Kaur, Sharanjeet; Mohamad, Zainal (Research Management Institute (RMI), 2012)
Background: In myopic eyes, the axial length of the globe exceeds normal dimensions, and the sclera becomes thinner, especially at the posterior pole. Therefore, the retina at the posterior pole may stretch in myopic eyes. Thus, it has been hypothesized that highly myopic eyes have thinner retinas as compared with emmetropic eyes. Problem statement: It is still controversial on the results of the correlation between the axial length, the retinal thickness and refractive error in healthy eyes. It may be because of the ocular dimensions are varies according to race. There is no study has been done to measure the correlation between the axial length, retinal thickness and refractive error among the Malay population. Objective: This research will be done to measure the correlation between the axial length, retinal thickness and refractive error of the healthy eyes among Malay students in UiTM. Methodology: A cross-sectional study will be conducted at Optometry Clinic, FSK, UiTM, which 45 UiTM students will be screened with history taking and preliminary tests to be a subject. The preliminary tests include visual acuity measurement using Snellen chart, Hirschberg test using pen torch, fundus examination using direct ophthalmoscope and anterior segment examination using slit lamp. The refractive error of the subject then will be objectively examined by autorefractor and will be refined subjectively. The retinal thickness will be measured using Optical Coherence Tomography (OCT) and the axial length will be measured using B-scan. Data will be analyzed using SPSS programme. Hypothesis: There are correlation between the axial length, retinal thickness and refractive error of healthy eyes among Malay students in UiTM. Outcomes: If this hypothesis is proven, these parameters should always be considered when assessing axial length progression, or retinal thickening, or refractive error progression among Malay population in future study.